Membaca Industri Pariwisata Bali Melalui Gerakan Sosial Kontra Hegemoni ForBALI - Nyoman Ayu Sukma Pramestisari (Politicos: Jurnal Politik Dan Pemerintahan, 2022)
The process of industrialization is often accepted as a perfect solution to alleviating the socio-economic problems of a region. Bali through the development of industry and tourism has succeeded in boosting the regional and national economy since its early development in 1980. But on the other hand, industrial dynamics also reflect the existence of production and reproduction of risk for the community such as the privatization of public space, desacralization, marginalization and exploitation of natural and human resources Starting from this problem, this research seeks to dissect how the Balinese people respond to the tourism industry climate through a movement platform. The ForBALI social movement as an effort to thwart the Benoa Bay reclamation program is a tangible manifestation that the Bali tourism industry is felt to have negative impact on the community. ForBALI resistance is a manifestation of the community’s counter hegemony to the oligarchs who try to continue to make efforts to perpetuate power under the pretext of economic growth and absorb labor. Interestingly, a counter discourse emerged from the pro-reclamation community of Benoa Bay departing from the view that development and being able to solve various social problems. The existence of these two groups for and against reclamation indicates that there is a dialectical process related to contestation in an effort to hegemony carried out by both parties.